Preface - Francois P. Retief; Louise Cilliers (Acta Theologica)
From text: This volume is the result of a most satisfying ongoing research project undertaken by a classicist and a physician over the past six years. Most of the articles are review works which bring together existing knowledge, placing the medical findings of the time in a broad historical context in order to give a better understanding of ancient medical views. One of the rewarding aspects of research of this kind is that thanks to modern information systems it is theoretically possible to gather virtually all the extant fragments of information on a specific subject — such as medicine — from the written sources of antiquity. Archaeology and modern science then often supplement the written information to ensure an optimal overview.